Analysis of Islamic Law and Law No. 56 PRP 1960 on the Practice of Pawning Paddy Fields in the Village of Malang - Hanik Musyarofah (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
This is field research entitled "Review of Islamic Law and Law Number 56 Prp of 1960 Against Pawn Pawn Practices in Jambesari Village, Poncokusumo District, Malang Regency". This study has two objectives, namely: how the practice of pawning rice fields in Jambesari Village, Poncokusumo District, Malang Regency and how to analyze Islamic law and Law no. 56 Prp Th. 1960 on the practice of pawning rice fields in Jambesari Village, Poncokusumo District, Malang Regency. The results of this study are that: first, the practice of pawning rice fields by the people of Jambesari Village, Poncokusumo District, Malang Regency is carried out by making an oral pawn agreement from both parties for a certain period; and second, the practice of pawning rice fields in Jambesari Village, Poncokusumo District, Malang Regency is in accordance with the opinion of the Hanafiyah scholars. However, contrary to the number of Maliki, Shafi'i and Hanbali scholars, it is mainly related to the use of pawned land which tends to have an element of coercion.